Papers - Solid Solubility of Mercury in Silver and in Gold (With Discussion) - H. M. Day; C. H. Mathewson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1938)
The constitution of the system silver-mercury has attracted the attention of many investigators during the last two decades, but since their results are for the most part in poor agreement, there is little need for a review of their individual contributions. It remained for the very careful thermal and microscopic investigation of Murphy1 in 1931 to give the constitutional diagram in its present and unquestioned form, which is shown in Fig. 1. He devised methods for taking cooling curves on alloys under high pressures and for the microscopic observation of alloys which contained liquid mercury as a structural constituent at ordinary temperatures. The compositions of the intermediate phases were confirmed and supplemented through X-ray analyses by Preston2 and Stenbeck.3 According to Murphy, at 2760 C. silver is able to dissolve 44 to 45 weight per cent of mercury, which may increase at lower temperatures to about 50 per cent. Preston concluded that the saturation boundary occurred at 46 ± 2 per cent at 100° C. From the values reported in the literature, these are the only ones that may be accepted as lying even in the right region. Preparation of Alloys The silver used in the present investigation was supplied by the United States Metals Refining Co. through the courtesy of the Committee on Industrial Uses of Silver and, since a complete spectrographic and chemical analysis was furnished, no attempt was made to purify it or to further establish the impurities present. The analyses reported by the company are shown in Table 1. Milligan4 has found that the magnesium content is probably less than 0.0005 per cent.